2004
DOI: 10.1093/sleep/27.3.395
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation of Strictly Episodic Memories Mainly Requires Rapid Eye Movement Sleep

Abstract: These results suggest that consolidation of truly episodic memories mainly involves REM sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 0 publications
8
88
1
2
Order By: Relevance
“…While this negative finding agrees with a recent study testing effects of early and late sleep on performance in a "remember/know" paradigm (Rauchs et al 2004), it appears to contrast with a number of foregoing studies indicating that various forms of nondeclarative memory, such as the procedural memory for skills (Plihal and Born 1997) and the priming of words and faces (Plihal and Born 1999;Wagner et al 2003) benefit in particular from REM sleeprich periods of sleep. Those studies led us to suppose a generalized benefit for REM sleep-rich periods of sleep for nondeclarative memories not depending on hippocampal function.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…While this negative finding agrees with a recent study testing effects of early and late sleep on performance in a "remember/know" paradigm (Rauchs et al 2004), it appears to contrast with a number of foregoing studies indicating that various forms of nondeclarative memory, such as the procedural memory for skills (Plihal and Born 1997) and the priming of words and faces (Plihal and Born 1999;Wagner et al 2003) benefit in particular from REM sleeprich periods of sleep. Those studies led us to suppose a generalized benefit for REM sleep-rich periods of sleep for nondeclarative memories not depending on hippocampal function.…”
Section: Discussionsupporting
confidence: 84%
“…Adopting a perspective beyond the framework of the processdissociation procedure, the present data would indicate that recognition of old words remains uninfluenced by sleep, but that after early sleep, the subject's ability to identify the correct list for congruent words is enhanced. This view appears to be in line with findings from a recent study that early SWS-rich sleep enhances memory for temporal context information in an episodic memory task (Rauchs et al 2004).…”
Section: Learning and Memory 47supporting
confidence: 90%
“…Sleep architecture changes have been observed in the night after training in a variety of tasks (for review, see Smith, 1995;Rauchs et al, 2005), but, to our knowledge, the learned association between a placebo treatment and analgesia has never been studied in relation to sleep. Nevertheless, the consolidation of episodic memories and the reprocessing of complex cognitive tasks have been linked previously with REM sleep alterations (Smith, 2001;Rauchs et al, 2004). In the current study, when positive expectations were accompanied by a consistent sensory experience before sleep (group 1), placebo responders specifically displayed a reduction in the amount of time they spent in REM sleep.…”
Section: Expectations and Rem Sleepmentioning
confidence: 99%
“…Whereas the learning of simple procedural skills has been linked to stage 2 sleep (Peters et al, 2007), rapid eye movement (REM) sleep appears to be specifically implicated in the processing of complex cognitive tasks (Smith, 2001) and emotional memories (Stickgold et al, 2001;Wagner et al, 2001). In addition, the consolidation of episodic memories seems to be mainly dependent on REM sleep (Rauchs et al, 2004), and memories encoded while awake have been shown to be reactivated during subsequent sleep periods in both animals (Pavlides and Winson, 1989;Wilson and McNaughton, 1994) and humans (Maquet et al, 2000;Peigneux et al, 2004). This sleep-dependent processing is proposed to allow for a reinterpretation of the meaning of novel information and to facilitate its integration into a network of related memories (Paller and Voss, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, insomnia or chronic loss of sleep is associated with excessive diurnal sleepiness and a decrease in psychomotor performance; being also affected the mood and functions of immune system (Malik & Kaplan, 2005). In this same way, in both animals and humans, it has been demonstrated that sleep, subsequent to a training period, improves execution of test (Stickgold et al, 2000) as well as memory consolidation (Fischer et al, 2002;Rauchs et al, 2004) whereas TSD or selective REM sleep deprivation (REMSD) impairs it considerably (Drummond & Brown, 2001;Nilsson et al, 2005;Smith et al, 2002). Although the exact way by which loss of sleep produces these negative cerebral effects is still unknown; it has been suggested that neuronal activity generated during prolonged periods of wakefulness can damage nervous cells and even induce cellular death (Inoué et al, 1995;Mamelak, 1997;Reimund, 1994).…”
Section: Biological Function Of Sleepmentioning
confidence: 99%